2016
DOI: 10.1016/j.cub.2016.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Fruitless Represses robo1 Transcription to Shape Male-Specific Neural Morphology and Behavior in Drosophila

Abstract: The Drosophila fruitless (fru) gene is regarded as a master regulator of the formation of male courtship circuitry, yet little is known about its molecular basis of action. We show that roundabout 1 (robo1) knockdown in females promotes formation of the male-specific neurite in sexually dimorphic mAL interneurons and that overexpression of the male-specific Fru(BM) diminishes the expression of Robo1 in the fly brain. Our electrophoretic mobility shift and reporter assays identify the 42-bp segment encompassing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 28 publications
1
88
0
1
Order By: Relevance
“…They suggest a model in which Fru M , acting via different isoforms, regulates sexually dimorphic expression of target genes that, individually, regulate different aspects of male courtship in a modular manner. This model is supported by a recent study from Yamamoto’s group in which they showed that the B isoform of Fru M represses robo1 in a specific cluster of neurons through a cis -regulatory sequence located in the promoter of robo1 [28•]. This results in a regulatory switch that guides these neurons down a male or female developmental pathway.…”
Section: Sexual Differentiation In Drosophila: the Search For Isoformmentioning
confidence: 65%
“…They suggest a model in which Fru M , acting via different isoforms, regulates sexually dimorphic expression of target genes that, individually, regulate different aspects of male courtship in a modular manner. This model is supported by a recent study from Yamamoto’s group in which they showed that the B isoform of Fru M represses robo1 in a specific cluster of neurons through a cis -regulatory sequence located in the promoter of robo1 [28•]. This results in a regulatory switch that guides these neurons down a male or female developmental pathway.…”
Section: Sexual Differentiation In Drosophila: the Search For Isoformmentioning
confidence: 65%
“…Bon was dispensable for FruM binding to the genomic sites, but HDAC1 and HP1a fail to bind to the FruM-positive sites in the absence of Bon, implying that FruM binds the site first, Bon binds the site second and then Bon recruits HDAC1 and/or HP1a. Ito et al 33 found that it is FruBM that removes Robo1 from male mAL neurons: FruBM binds to the robo1 promoter to repress its transcription. The likely scenario is that a FruM-containing complex switches chromatin states, thereby silencing or activating a large set of genes that are required in neurons for taking on the female or male fate ( Figure 2D).…”
Section: All-or-none Sex Switching By Chromatin Remodelingmentioning
confidence: 99%
“…The likely scenario is that a FruM-containing complex switches chromatin states, thereby silencing or activating a large set of genes that are required in neurons for taking on the female or male fate ( Figure 2D). 33 Pal1 contains the motif proposed as a FruM binding sequence by Neville et al 29 but does not contain any motif proposed by Dalton et al 35 Ito et al 33 discovered that a small deletion of a several base pair region in Pal1 of the robo1 promoter (eg, a 6 bp deletion occurring in the robo1 Δ1 allele) not only increased the number of male flies with no male-specific neurite but also impaired the male courtship posture, even in the flies carrying only one copy of the mutation, that is, heterozygotes. This result implies that Robo1 normally inhibits the ipsilateral neurite formation in females, whereas this Robo1-dependent inhibition is removed in males, allowing them to develop the ipsilateral neurite in mAL neurons ( Figure 3B).…”
Section: All-or-none Sex Switching By Chromatin Remodelingmentioning
confidence: 99%
See 2 more Smart Citations